The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1475-2891-13-91
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional interventions for the adjunctive treatment of schizophrenia: a brief review

Abstract: Schizophrenia is a chronic condition that impacts significantly not only on the individual and family, but the disorder also has wider consequences for society in terms of significant costs to the economy. This highly prevalent condition affects approximately 1% of the worldwide population, yet there are few therapeutic options. The predominant treatment strategy for schizophrenia is anti-psychotic medication (with or without additional talking therapy) even though this approach lacks efficacy in managing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 105 publications
(106 reference statements)
0
51
0
4
Order By: Relevance
“…Curcumin, however, distinguishes from ketamine and likely esketamine with its potential antipsychotic effects as shown in our study with oral formulation of curcumin as curcumin C-3 complex (66). Furthermore, the benefits of curcumin in reducing the depressive symptoms have been reported in 6 randomized controlled studies in patients diagnosed as depressive disorders [76].…”
Section: Lipocurc Tm Infusion: Lead Drug On the Horizon For Schizophrmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin, however, distinguishes from ketamine and likely esketamine with its potential antipsychotic effects as shown in our study with oral formulation of curcumin as curcumin C-3 complex (66). Furthermore, the benefits of curcumin in reducing the depressive symptoms have been reported in 6 randomized controlled studies in patients diagnosed as depressive disorders [76].…”
Section: Lipocurc Tm Infusion: Lead Drug On the Horizon For Schizophrmentioning
confidence: 99%
“…Curcumin, however, distinguishes from ketamine and likely esketamine with its potential antipsychotic effects as shown in our study with oral formulation of curcumin as curcumin C-3 complex (66). Furthermore, the benefits of curcumin in reducing the depressive symptoms have been reported in 6 randomized controlled studies in patients diagnosed as depressive disorders [76].These considerations lead us to entertain seriously that organizing and conducting Phase II of LipocurcTM in schizophrenia open a new chapter translating recent advances in epigenetics -based, NMDA-and inflammation pathways, coupled with nanotechnology in drug delivery, towards developing and optimizing novel therapeutics in managing the devastating consequences of schizophrenia. It is somewhat disconcerting that a recent meta-analysis of TRS schizophrenia shows that the response rate to clozapine is about 40 % with 25 % reduction in the PANSS (Positive and Negative Syndrome Scale [77].…”
mentioning
confidence: 99%
“…w obecności przeciwciał antygliadynowych [80]. W małym badaniu na próbie 8 pacjentów, którzy nie wykazywali objawów nadwrażliwości, żaden z nich nie uzyskał korzyści płynących z diety bezglutenowej i dodatkowo pozbawionej produktów mlecznych [107,108]. W opisach poszczególnych przypadków pacjentów, którzy prezentowali objawy chorób glutenozależnych, poprawa po wprowadzeniu GFD obserwowana była zawsze.…”
Section: Rola Diety W Leczeniuunclassified
“…in the presence of gliadin antibodies [80]. In a small study on a sample of 8 patients who showed no symptoms of gluten sensitivity, none of them experienced the benefits of a glutenfree and additionally devoid of dairy products diet [107,108]. In the descriptions of individual cases of patients who presented symptoms of gluten-dependent disorders, improvement after the introduction of GFD was always observed.…”
Section: The Role Of Diet In the Therapymentioning
confidence: 99%
“…Несмотря на первичные обнаде-живающие результаты, дальнейшие клинические исследо-вания, аналогично таковым при аутизме, продемонстриро-вали довольно противоречивые результаты в отношении эффективности безглютеновой диеты при шизофрении, указывая в том числе на то, что, вероятно, существует отдельная группа больных, для которых диетотерапия явля-ется эффективной [34][35][36]. Несмотря на существующую необходимость дополнительных исследований в отношении диетотерапии, безглютеновая диета в настоящее время все же рассматривается как возможное эффективное дополне-ние к стандартной терапии при шизофрении согласно современным рекомендациям [37].…”
unclassified